Causes of Female Labor Migration in Nepal - Yadav, Shiva Kumar (Patan Prospective Journal, 2022)
This is related with female labor migration in Sindhupalchowk District in Nepal. Foreign labor migration is a global phenomenon that dates back to the time when payment in return for labor was first introduced. There is no country in the world where foreign labor migration has not occurred. However, economic globalization has speeded up the process way beyond its normal pace. Fast economic growth and slow economic development made people in poorer countries migrate for a better life. While previously only men used to migrate in search of employment, recently, women are leaving for foreign employment as well. Such migration for employment has added value to the national income of the country in the form of remittance. Most of the developing countries are thriving on remittance. Labor exportation has been an important solution for internal unemployment for developing countries. It is a major source of foreign exchange. Therefore, countries like the Philippines and Indonesia have integrated labor export as part of their development strategies. In case of Nepal, remittance helped sustain the economy throughout the conflict period and it continues to be so. Nepal has adopted an open policy towards foreign labor migration. Currently, there are 108 countries approved by the Nepal government for foreign labor migration. The paper was prepared on the basis of 40 households.